2021
DOI: 10.1177/23294965211001394
|View full text |Cite
|
Sign up to set email alerts
|

Individual Vulnerability and Organizational Context as Risks for Sexual Harassment among Female Graduate Students

Abstract: Despite a growing body of work on sexual harassment among college students, little work has examined predictors of sexual harassment specifically among graduate students. This study aims to address this gap in the literature by using data from 490 female graduate students at a large, public university. Based on a feminist routine activity theory approach, both individual vulnerability (lesbian, gay, bisexual, queer, or other sexual identity [LGBQ+], international student status, psychological distress, alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…On the other hand, female students tend to identify a broader range of behaviors as sexual harassment than male students (Rotundo et al, 2001; Rosenthal et al, 2016). Females are usually more vulnerable to sexual harassment (Sutton et al, 2021), which may allude to why they have a broad list of what qualifies as sexual harassment—for self-protection.…”
Section: Understanding Of Sexual Harassmentmentioning
confidence: 99%
“…On the other hand, female students tend to identify a broader range of behaviors as sexual harassment than male students (Rotundo et al, 2001; Rosenthal et al, 2016). Females are usually more vulnerable to sexual harassment (Sutton et al, 2021), which may allude to why they have a broad list of what qualifies as sexual harassment—for self-protection.…”
Section: Understanding Of Sexual Harassmentmentioning
confidence: 99%
“…Scholars have reported that women are frequently subject to SH ( Huerta et al, 2006 ). As the industry is deeply rooted in hyper-masculine tendencies ( Sullivan, 2021 ), it is largely men who perpetrate SH ( Parent et al, 2016 ; Ford and Ivancic, 2020 ; Sutton et al, 2021 ) and negatively influence females ( Omorogiuwa, 2018 ). An organizational climate (OC) is an expression of individuals’ common views and mechanisms that explains how certain activities are geared toward achieving SH goals ( Fasting et al, 2010 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…One study found that 38% of women and 23.4% of men graduate students experienced sexual harassment from faculty or staff, and 58% of women and 39% of men graduate students experienced sexual harassment from other students (Rosenthal et al, 2016). More recently, a study found that being a female graduate student with an LGBTQIA+ identity was the strongest predictor of harassment, and women who identified as a racial minority experienced harassment at the intersection of these inextricably linked identities (Sutton et al, 2021). Broadly, organizational contexts such as departmental support, female ratio within a department, and the department being situated within a male-dominated field of study may play a role in graduate workers' risk of harassment.…”
Section: Academic Discipline As the Context For Academic Violencementioning
confidence: 99%
“…Broadly, organizational contexts such as departmental support, female ratio within a department, and the department being situated within a male-dominated field of study may play a role in graduate workers' risk of harassment. Specifically, female graduate students are more at risk of being sexually harassed by peers if they are in a male-dominated field (Sutton et al, 2021). However, certain academic disciplines may provide protective factors to those who abuse and/or may leave graduate workers more vulnerable due to the discipline context.…”
Section: Academic Discipline As the Context For Academic Violencementioning
confidence: 99%
See 1 more Smart Citation